Social Goals and Planning of Science - Planning Commission (Planning Commission, 1977)
In the formulation and implementation of R&D policy, social and cultural factors, which are often ignored as unimportant, are as significant as any of the purely technical factors. However, the linkage between the policy and these factors is neither causal nor limited to the contemporary period. The linkages go back in history and are interwoven in a manner which makes their full appreciation rather difficult.
Chief Planning & Head Centre for the Study of Science,Technology and Development